Remission induction comparing infliximab and high-dose intravenous steroid, followed by treat-to-target: a double-blind, randomised, controlled trial in new-onset, treatment-naive, rheumatoid arthritis (the IDEA study). Issue 1 (2nd August 2013) - Nam, J L; Villeneuve, E; Hensor, E M A; Conaghan, P G; Keen, H I; Buch, M H; Gough, A K; Green, M J; Helliwell, P S; Keenan, A M; Morgan, A W; Quinn, M; et al.
Abstract : Objectives: In disease modifying antirheumatic drug (DMARD)-naive early rheumatoid arthritis (RA), to compare the efficacy of methotrexate (MTX) and infliximab (IFX) with MTX and intravenous corticosteroid for remission induction. Methods: In a 78-week multicentre randomised controlled trial, double-blinded to week 26, 112 treatment-naive RA patients (1987 American College of Rheumatology classification criteria) with disease activity score 44 (DAS44)>2.4 were randomised to MTX + IFX or MTX + single dose intravenous methylprednisolone 250 mg. A treat-to-target approach was used with treatment escalation if DAS44>2.4. In the IFX group, IFX was discontinued for sustained remission (DAS44<1.6 for 6 months). The primary outcome was change in modified total Sharp-van der Heijde score (mTSS) at week 50. Results: The mean changes in mTSS score at week 50 in the IFX and intravenous steroid groups were 1.20 units and 2.81 units, respectively (adjusted difference (95% CI) −1.45 (−3.35 to 0.45); p=0.132). Radiographic non-progression (mTSS<2.0) occurred in 81% vs 71% (OR 1.77 (0.56 to 5.61); p=0.328). DAS44 remission was achieved at week 50 in 49% and 36% (OR 2.13 (0.91 to 5.00); p=0.082), and at week 78 in 48% and 50% (OR 1.12 (0.47 to 2.68); p=0.792). Exploratory analyses suggested higher DAS28 remission at week 6 and less ultrasound synovitis at week 50 in the IFX group. Of the IFX group, 25% (14/55) achieved sustained remission and stopped IFX. No substantive differences in adverse events were seen. Conclusions: In DMARD-naive early RA patients, initial therapy with MTX+high-dose intravenous steroid resulted in good disease control with little structural damage. MTX+IFX was not statistically superior to MTX+intravenous steroid when combined with a treat-to-target approach.